Peran Profitabilitas pada Pengaruh Green Accounting terhadap Nilai Perusahaan - Riska Alfiana; Sari Andayani; Condro Widodo (Akuisisi : Jurnal Akuntansi, 2026)
This research was conducted with the aim of determining the influence of green accounting as the independent variable and firm value as the dependent variable, with profitability as a mediating variable, in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. The sample used in this study consists of 156 observational data points, determined through purposive sampling. The method used to analyze the research data is panel regression analysis, tested using Eviews12 statistical software. Based on the regression results, the implementation of green accounting does not affect firm value or profitability. Profitability has a significant effect on firm value but does not mediate the relationship between green accounting and firm value.